2021
DOI: 10.3390/ijerph182211950
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Effects of Spatial Heterogeneities and Layered Exposure Interventions on the Spread of COVID-19 across New Jersey

Abstract: COVID-19 created an unprecedented global public health crisis during 2020–2021. The severity of the fast-spreading infection, combined with uncertainties regarding the physical and biological processes affecting transmission of SARS-CoV-2, posed enormous challenges to healthcare systems. Pandemic dynamics exhibited complex spatial heterogeneities across multiple scales, as local demographic, socioeconomic, behavioral and environmental factors were modulating population exposures and susceptibilities. Before ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…[43][44][45] Combining several layers of interventions can not only cover up these gaps but also further enhance each layer. [46][47][48] Our study shows that face mask use can be cost-effective and, in many cases, cost saving, meaning that face mask use would pay for itself. This finding provides strong support for governments, third-party payers, and other organisations to provide face masks to the general public.…”
Section: Discussionmentioning
confidence: 72%
“…[43][44][45] Combining several layers of interventions can not only cover up these gaps but also further enhance each layer. [46][47][48] Our study shows that face mask use can be cost-effective and, in many cases, cost saving, meaning that face mask use would pay for itself. This finding provides strong support for governments, third-party payers, and other organisations to provide face masks to the general public.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the ML models “learned” a steeper increasing trend for % minority below 20%; this corresponds to a situation when the exponential assumption is violated. The ML models also “learned” that COVID-19 mortality rates increase with population density at the lower range but become “saturated” at higher densities [ 34 ], a fact that cannot be captured by geostatistical models with “naive” structures.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…An association metric was also constructed to approximate effects captured by the ML models and showed that ML (even for small datasets) played a complementary role to advanced geostatistical models: those models can capture similar associations when an underlying exponential relation holds, but ML can further “learn” non-exponential patterns in the data, an attribute that is important for knowledge discovery. For instance, RF and XGBOOST detected nonlinear saturation effects of increasing population density that can be explained by the combined effects of “density-dependent” and “frequency-dependent” mechanisms [ 34 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is challenging to accurately predict the drastic fluctuations in the actual numbers of infections and deaths due to changing external factors. In [6][7][8][9], the traditional Susceptible, Exposed, Infected, Recovered (SEIR) model was combined with some external factors such as quarantine, vaccination and other strategies for the prediction of the COVID-19 epidemic, and they achieved good results, but the parameters of the model, such as the mutation rate of the virus, the probability of recovery, etc., change dynamically during the evolution of the epidemic, and these models do not take this feature into account. So, there are still some problems.…”
Section: Literature Reviewmentioning
confidence: 99%